PENCIPTAAN KEUNGGULAN BERSAING PERUSAHAAN MELALUI INOVASI - Hendriyanto, Asepta (Jurnal Ilmu Manajemen dan Akuntansi Terapan (JIMAT), 2014)
The purpose of this research is to investigate and analyze the factors that affect the competitive advantage through product innovation. The method used is the method of survey data obtained directly through questionnaires. Sampling using sensus sampling methods and methods of analysis used in this research was the path analysis. Â Based on the research results revealed that human capital, and entrepreneur orientation have effect on innovation. And variable innovation, have effect of the firm competitive advantage